2014
DOI: 10.1097/jan.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

Stresses, Strengths, and Experiences of Mothers Engaged in Methadone Maintenance Treatment

Abstract: Although methadone maintenance treatment (MMT) is the intervention of choice for addiction, unfortunately, mothers are less likely to engage in care. Greater understanding of how mothers experience the addiction and the recovery process is needed to develop strategies to effectively engage mothers in MMT. This mixed method study applied quantitative and qualitative approaches with a sample of 12 mothers who were engaged in MMT for 3 or more months. Although the results showed stresses of high depression and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Motherhood is a complex state that has been underexplored in mental health. Initial studies show, on the one hand, that parenting may be considered as a very relevant motivation for seeking treatment and improving health behaviors in women [ 1 , 2 ]. Therefore, motherhood has been considered as an internal facilitating factor, given that most women with mental illnesses report the desire to be good mothers and to take care of their children in the best possible way [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Motherhood is a complex state that has been underexplored in mental health. Initial studies show, on the one hand, that parenting may be considered as a very relevant motivation for seeking treatment and improving health behaviors in women [ 1 , 2 ]. Therefore, motherhood has been considered as an internal facilitating factor, given that most women with mental illnesses report the desire to be good mothers and to take care of their children in the best possible way [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…To involve mothers in MMT, we must understand how mothers experience addiction and recovery. 35 Child protection system engagement was substantially related to mental health issues, parental support, and child number. 93 Mothers gradually become aware of the impact of addiction on their ability to be good mothers and choose rehabilitation and MMT to benefit their children and preserve their identity.…”
Section: Resultsmentioning
confidence: 99%
“…Motherhood was an important identifying factor for women, and despite not having children in the home, women were motivated to enter methadone treatment to facilitate access to their children. Similarly, Secco et al (2014) found that women entered treatment to retain custody of children and build relationships with them. The current study findings expand those of Secco et al, as even when children are taken from a woman's custody, they are still a primary motivating factor influencing treatment seeking.…”
Section: Discussionmentioning
confidence: 99%